PySide GUI Application Development - Second Edition. - Jaganmohan, Gopinath; Loganathan, Venkateshwaran (Packt Publishing, Limited, 2016)
Develop more dynamic and robust GUI applications using PySide, an open source cross-platform UI frameworkAbout This Book Designed for beginners to help you get started with GUI application development Develop your own applications by creating customized widgets and dialogs Written in a simple and elegant structure so you easily understand how to program various GUI componentsWho This Book Is ForThis book is written for Python programmers who want to learn about GUI programming. It is also suitable for those who are new to Python but are familiar with object-oriented programming. What You Will Learn Program GUI applications in an easy and efficient way Download and install PySide, a cross-platform GUI development toolkit for Python Create menus, toolbars, status bars, and child windows Develop a text editor application on your own Connect your GUI to a database and manage it Execute SQL queries by handling databasesIn DetailElegantly-built GUI applications are always a massive hit among users. PySide is an open source software project that provides Python bindings for the Qt cross-platform UI framework. Combining the power of Qt and Python, PySide provides easy access to the Qt framework for Python developers and also acts as an excellent rapid application development platform. This book will take you through everything you need to know to develop UI applications. You will learn about installing and building PySide in various major operating systems as well as the basics of GUI programming. The book will then move on to discuss event management, signals and slots, and the widgets and dialogs available with PySide. Database interaction and manipulation is also covered. By the end of this book, you will be able to program GUI applications efficiently and master how to develop your own applications and how to run them across platforms. Style and approachThis is an accessible and practical guide to developing GUIs for Python applications.